Exploring the Architecture and Its Influence of Badshahi Mosque Lahore (Bmlh): A Unesco Tentative Heritage Site - Saddam Hussain; Fu Juan (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Asia has a variety of diverse ancient cultures and civilizations. In this paper, we studied the architecture of a UNESCO tentative heritage site: Badshahi Mosque Lahore (BMLH, 1671–1673), built by the Mughal emperor Aurangzeb Alamgir (AA). The site is special since it had the largest mosque title (human capacity = 100,000) in the world from 1673 to 1986, has great architectural importance, and is one of the most popular tourist attractions in the world. Various mosque architectures (MA) emerged over the past 1400 years worldwide to preserve each region's diversity, identity, and culture. A documentation visit was arranged to study this site and feel the real architecture of the Mughals after decades of preserved form. The study found that BMLH underwent significant alterations while keeping the original MA. This unique study further focused on the basic architecture of the Mughal Era. A detailed study of the architectural themes of BMLH showed that the architectural style of this heritage included regional, cultural, and traditional impacts. By analyzing the architectural themes and distinctive features of BMLH, we have uncovered the distinct regional, religious, and psychological influences that led to Mughal-era mosque architecture's development. Further documentation was reported about the current structural situation of Badshahi Mosque; the number of seepages has been pointed out, and several decays were sighted during our visit. For this significant site's perfect preservation, it was proposed that high-end preservation strategies be implemented in the future.